2009
DOI: 10.1007/s10681-009-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to corn leaf aphid (Rhopalosiphum maidis Fitch) in tropical corn (Zea mays L.)

Abstract: Corn leaf aphids (Rhopalosiphum maidis Fitch) are found throughout the year on maize in Hawaii and occasionally cause yield loss. Sweet corn inbred Hi38-71 was observed to have high field resistance to aphids and was chosen for this genetic study. An artificial infestation technique was developed using hair-pin clip cages (2.2 cm diameter) which we devised and built. The cages were applied to field-grown plants into which three wingless viviparous adults were placed. Aphid populations were classified on a 1-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
0
21
1
4
Order By: Relevance
“…All these results suggest that the differences in aphid abundance obtained are better accounted for by the background of the varieties and the year conditions than by the transgenesis or Event itself. Differences in aphid performance due to maize varietal characteristics have been reported (Carena and Glogoza 2004;So et al 2010) but to fully understand and range the differences observed in the present study a wider baseline information for comparing would be necessary. Transgenic Bt maize did not alter the aphidparasitoid associations and had no effect on the aphid parasitism rates.…”
Section: Discussionmentioning
confidence: 91%
“…All these results suggest that the differences in aphid abundance obtained are better accounted for by the background of the varieties and the year conditions than by the transgenesis or Event itself. Differences in aphid performance due to maize varietal characteristics have been reported (Carena and Glogoza 2004;So et al 2010) but to fully understand and range the differences observed in the present study a wider baseline information for comparing would be necessary. Transgenic Bt maize did not alter the aphidparasitoid associations and had no effect on the aphid parasitism rates.…”
Section: Discussionmentioning
confidence: 91%
“…The average number of aphids per plant was used as a basis for identifying aphid resistance in bean (Han et al 1991). There is evidence for genetic control of aphid resistance in many crops, including tomato (Solanum lycopersicum) (Rossi et al 1998), wheat (Triticum aestivum) (Liu et al 2005), barley (Hordeum vulgare) (Mittal et al 2008), melon (C. melo) (Sarria et al 2008;Brotman et al 2002), barrel clover (Medicago truncatula) (Klingler et al 2005), maize (Zea mays) (So et al 2010) and soybean (Glycine max) (Kim et al 2010a, b;Ohnishi et al 2012). However, little is known about the inheritance of aphid resistance in cucumber.…”
Section: Introductionmentioning
confidence: 99%
“…), eight independent dominant genes each confer resistance to the Russian wheat aphid (Diuraphis noxia) from different resistance sources (Liu et al 2005), while one recessive gene contributes to the resistance in Triticum tauschii line SQ24 (Nkongolo et al 1991). A single recessive gene was also found to control resistance to corn leaf aphid (Rhopalosiphum maidis Fitch) (So et al 2010) and the groundnut rosette disease vector, Aphis craccivora, infesting peanut (Herselman et al 2004).…”
Section: Introductionmentioning
confidence: 99%